A clinical study of outcome of neoadjuvant chemotherapy in 30 cases of locally advanced breast carcinoma - Sonvane, Shwetal Ravindrabhai; Pancholi, Mukesh; Sharma, Akhil (International Surgery Journal, 2019)
Background: Locally advanced breast cancer presents with a difficult management problem. It remains a challenge to achieve local and distant control of locally advanced breast cancer. Over the last decade preoperative/ neoadjuvant chemotherapy has emerged as the standard of care for these patients. Successful reduction in the size of the tumor is associated with increased rate of operability. The objective of this study is to observe the response of neoadjuvant chemotherapy in locally advanced breast carcinoma in form of outcome and complications. The outcome is measured as down staging or downgrading of tumor, results of surgery and its complications, disease free survival and recurrence. Methods: This is the observational prospective study of consecutive 30 cases of locally advanced breast cancer admitted in department of general surgery during a period from May 2017 to August 2018 at new civil hospital, Surat. Neo adjuvant chemotherapy were given every three weekly and the response of therapy calculated in form of reduction in the size of tumor or getting the margin free from skin or pectoral muscles or reduction in the axillary lymph node mass. Results: In this study about 93% of cases responded to neoadjuvant chemotherapy with 10% of cases shows complete clinical response where tumor becomes completely free from skin or pectoral muscles or negative axillary lymph nodes. Conclusions: With the evidence from the literature and study conducted earlier, our observations of clinical response of neoadjuvant chemotherapy in patients with locally advanced breast cancer had corroborative evidence.